Automated serviceability prediction of NSM strengthened structure using a fuzzy logic expert system - Darain, K.M.U.; Jumaat, Mohd Zamin; Hossain, M.A.; Hosen, M.A.; Obaydullah, M.; Huda, M.N.; Hossain, I. (Expert Systems with Applications, 2015)
This paper presents a simplified model using a fuzzy logic approach for predicting the serviceability of reinforced concrete (RC) beams strengthened with near surface mounted (NSM) reinforcement. Existing analytical models lack proper formulations for the prediction of deflection and crack width in NSM strengthened beams. These existing models are based on the externally bonded reinforcement (EBR) technique with fiber reinforced polymer (FRP) laminates, which presents certain limitations for application in predicting the behavior of NSM strengthened beams. In this study seven NSM strengthened RC beams were statically tested under four point bending load. The test variables were strengthening material (steel or CFRP) and bond length (1600, 1800 or 1900 mm). For fuzzification, load and bonded length were used as input parameters and the output parameters were deflection and crack width for steel bar and CFRP bar. Experimentally NSM steel strengthened beams showed better performance in terms of crack width and stiffness, although NSM FRP strengthened beams exhibited enhanced strength increment. For all parameters, the relative error of the predicted values was found to be within the acceptable limit (5) and the goodness of fit of the predicted values was found to be close to 1.0. Hence, the developed prediction system can be said to have performed satisfactorily. (C) 2014 Elsevier Ltd. All rights reserved.